2012
DOI: 10.1542/peds.2012-0333
|View full text |Cite
|
Sign up to set email alerts
|

FDA’s Health Claim Review: Whey-protein Partially Hydrolyzed Infant Formula and Atopic Dermatitis

Abstract: In this review, we explain how the US Food and Drug Administration (FDA) used its evidence-based review system to evaluate the scientific evidence for a qualified health claim for 100% whey-protein partially hydrolyzed infant formula (W-PHF) and reduced risk of atopic dermatitis (AD). The labeling of health claims, including qualified health claims, on conventional foods and dietary supplements require premarket approval by the FDA. Health claims characterize the relationship between a substance (food or food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Whey preparations, being a source of high quality protein and of active peptides, are widely used by manufacturers of baby foods [Chung & Yamini, 2012;Lloyd, 2002;Murphy et al, 2015]. It is a standard procedure to establish an appropriate ratio of whey proteins to casein, which in the case of whey-based supplements should reach 60:40, i.e.…”
Section: Other Uses Of Whey In the Food Industrymentioning
confidence: 99%
“…Whey preparations, being a source of high quality protein and of active peptides, are widely used by manufacturers of baby foods [Chung & Yamini, 2012;Lloyd, 2002;Murphy et al, 2015]. It is a standard procedure to establish an appropriate ratio of whey proteins to casein, which in the case of whey-based supplements should reach 60:40, i.e.…”
Section: Other Uses Of Whey In the Food Industrymentioning
confidence: 99%
“…[The] FDA has concluded that the relationship between 100% Whey-Protein Partially Hydrolyzed infant formulas and the reduced risk of atopic dermatitis is uncertain, because there is very little scientific evidence for the relationship" [22,23] .…”
Section: Hydrolyzed Formulas and Primary Eczema Preventionmentioning
confidence: 99%
“…The German Infant Nutritional Intervention Study [35] found that infants fed extensively hydrolyzed casein formula for the first 4 months had reduced rate of atopic dermatitis at 1 year of age compared with infants fed cow's milk formula (CMF) ( Table 3) [35][36][37][38][39][40][41][42]. Interestingly, the rate of food-induced urticaria was higher in the extensively hydrolyzed casein formula group (1.4 vs. 0.4% but no P value is reported).…”
Section: Milkmentioning
confidence: 99%
“…A meta-analysis, examining the utility of partially hydrolyzed whey formula (W-pHF) in the prevention of allergy, found that infant-fed W-pHF had reduced atopic dermatitis at 4-6 and 12 months but not at 24 months, and 30-36 months [37]. The Food and Drug Administration concluded that there is little evidence to support the relationship between intake of W-pHF and reduced risk of atopic dermatitis up to 3 years of age [38]. Since then, an additional study by Lowe et al [39] revealed that infants fed W-pHF were not at lower risk of eczema and food reactions in the first 2 years after birth compared with CMF.…”
Section: Milkmentioning
confidence: 99%